Mitochondrial dysfunction during disease progression in Barrett's oesophagus - O'Farrell, Naoimh (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2014)
Barrett’s oesophagus is the leading risk factor for oesophageal adenocarcinoma. However, it is difficult to identify patients at risk of disease progression. Mitochondria are highly susceptible to mutations due to high levels of reactive oxygen species (ROS) coupled with low levels of DNA repair. The timing and functional relevance of mitochondria mutagenesis and dysfunction during Barrett’s oesophagus progression is unknown.
Keywords: Surgery, Ph.D.; Ph.D. Trinity College Dublin